The Land Snails of Arkansas - Leslie Hubricht (Hello World!, 1972)
This paper reports the land snail records for Arkansas as represented by specimens in the collection of the author. For western Arkansas it is fairly complete for the larger species, but for the small species more collecting needs to be done. For some of the small species it is necessary to be there after a rain to collect them. This is difficult when one must plan collecting trips months in advance. The Mississippi Delta which occupies the eastern half of the State, for the most part, is either under cultivation or is swamp; and land snails are difficult to find. As a result there are few records for the Delta and these are of widely distributed species.